Immunisation coverage and its associations in rural Tanzanian infants - Kruger, C.; Olsen, O.; Mighay, E.; Ali, Mohammed (Australian Rural Health Education Network, 2013)
Introduction: In Tanzania, vaccination rates (VRs) range from 80% to 90% for standard vaccines, but little information is available about rural populations and nomadic pastoralists. This study investigates levels and trends of the immunisation status of infants at eight mobile reproductive-and-child-health (RCH) clinics in a rural area in northern Tanzania (with a large multi-tribal population that has a significant population of nomadic pastoralists) for the years 1998, 1999, 2006 and 2007. In addition, the influence of tribal affiliation and health system-related factors on the immunisation status in this population is analysed. Methods: Vaccination data of 3868 infants for the standard bacillus Calmette–Guérin (BCG), poliomyelitis, diphtheria, pertussis, tetanus and measles vaccines were obtained from the RCH clinic records retrospectively, and coverage for both single vaccines and full vaccination by the end of first year of life were calculated. These results were correlated with data on predominant tribal affiliation at the clinic site, skilled attendance at birth, service provision and vaccine availability as independent variables.Results: In 1998, the full vaccination rate (FVR) across all RCH clinics was 72%, significantly higher than in the other years (1999: 58%; 2006: 58%; 2007: 57%) (p<0.0001). BCG and measles VRs were highest in 1998 and 1999, whereas VR was lowest for poliomyelitis in 1999, and for diphtheria–pertussis–tetanus in 2007 (all p<0.001). Measles VR showed a declining trend (1998: 72%; 1999: 73%; 2006: 62%; 2007: 59%) affecting the FVR, except in 1999 when poliomyelitis VR was lower (67%). FVR > 80% was only achieved at one clinic during 3 years. No clinic showed a consistent increase of VRs over time. In univariate analysis, predominant tribal affiliation (Datoga tribe) was associated with a low FVR (odds ratio (OR) 4.6 (95% confidence interval (CI) 3.8–5.5)), as were low rates of skilled attendance at birth (OR 3.6 (CI 2.9–4.4)). Other health system-related factors associated with low FVRs included interruption of scheduled monthly immunisation clinics (OR 9.8 (CI 2.1–45.5)) and lack of vaccines (OR 1.2–2.9, depending on vaccine). In multivariate analysis, predominant Datoga tribal affiliation and lack of vaccines retained their association with the risk of low rates of vaccination. Conclusions: Vaccination rates in this difficult-to-reach population are markedly lower than the national average for almost all years and clinics. Affiliation to the nomadic Datoga tribe and lack of vaccines determine VRs in this rural population. Improvements in immunisation service delivery, vaccine availability, stronger involvement of the nomadic communities and special outreach services for this population are required to improve VRs in these remote areas of Tanzania.